On holomorphic projection for symplectic groups - Maurischat, Kathrin (Journal of number theory, 2018)
We construct certain Casimir operators and study the spectral properties of their resolvents on L2(Γ\Sp2(R)). We define non-holomorphic multi-variable Poincaré series of exponential type for symplectic groups and continue them analytically in case of genus two for the small weight four using the above resolvents. We apply our results to describe the holomorphic projection to the weight four holomorphic discrete series in terms of Fourier coefficients by using Sturm's operator. This paper is a study of a prototype for symplectic groups and special orthogonal groups.